Effect of Glyphosate Spray on Seed Yield and Quality Attributes in Watermelon (Citrullus vulgaris) cv Sugar Baby - N.K. CHOPRA; NISHA CHOPRA; S.N.SINHA; VINOD KUMAR (Seed Research, 2026)
Efficacy of glyphosate (nonselective herbicide) against obnoxious weeds by adopting a new spraying technique and its subsequent effect on seed yield and its quality was evaluated in watermelon at research farm, Indian Agricultural Research Institute, Kanal during summer season of 2000 and 2001. Glyphosate being non residual and translocated herbicide was applied on weed foliage after covering the watermelon plants fully with plastic pots 20 days after sowing. Glyphosate (1.0 and 0.5%) reduced the weed density and weed dry weight significantly over two and one hand weeding and weed check. Application of glyphosate 1.0% alongwith one hoeing inc increased the fruit and seed yield significantly over check, two hand weeding and one hand weeding. Seed yield remained significantly at par under different levels of glyphosate. Seed quality in terms of per cent germination was not affected due to different weed control treatments However, 1000 seed weight, seedling dry weight and vigour index was maximum with glyphosate 1.0% compared to weed check and one hand weeding.